Study on gaseous impurities in alpha-alumina, used single crystals growing - Blank, T.A.; Eksperiandova, L.P.; Gorodilova, L.I.; Panikarskaya, V.D.; Kudin, K.A. (Functional Materials, 2005)
The optimal condition of water content determination in α-AI₂О₃, including sample mixing with methanol followed by titration of the suspension with K.Fisher reagent in the presence of methylene-blue background dye have been found. We have proved the absence of any significant systematic errors by variation of weighed. The determination limit, corresponding to standard deviation of single result 0.3, of the methodic developed is 9•10⁻² mass %. Thermogravimetric and mass-spectrometric data show that α-AI₂О₃ contains not only water, but also significant amounts of СО and СО₂, which, apparently, is the main reason of blowhole-like defects in those single crystals. We assume that material degassing by heating it in vacuum can allow a more effective elimination of such defects in the crystals, than the widely used thermal treatment of the material at atmospheric pressure.